Evidence for concerted movement of nuclear and mitochondrial clines in a lizard hybrid zone. Issue 8 (18th February 2017) - Leaché, Adam D.; Grummer, Jared A.; Harris, Rebecca B.; Breckheimer, Ian K.
Abstract: Moving hybrid zones provide compelling examples of evolution in action, yet long‐term studies that test the assumptions of hybrid zone stability are rare. Using replicated transect samples collected over a 10‐year interval from 2002 to 2012, we find evidence for concerted movement of genetic clines in a plateau fence lizard hybrid zone ( Sceloporus tristichus ) in Arizona. Cline‐fitting analyses of SNP and mtDNA data both provide evidence that the hybrid zone shifted northward by approximately 2 km during the 10‐year interval. For each sampling period, the mtDNA cline centre is displaced from the SNP cline centre and maintaining an introgression distance of approximately 3 km. The northward expansion of juniper trees into the Little Colorado River Basin in the early 1900s provides a plausible mechanism for hybrid zone formation and movement, and a broadscale quantification of recent land cover change provides support for increased woody species encroachment at the southern end of the hybrid zone. However, population processes can also contribute to hybrid zone movement, and the current stability of the ecotone habitats in the centre of the hybrid zone suggests that movement could decelerate in the future.